Corporate Social Responsibility (CSR), Sustainability and ESG Standards Used by ATHEX ESG Index Listed Companies - Triantafyllos Papafloratos; Garyfallos Fragidis (Standards, 2025)
Corporate social responsibility (CSR) and sustainability have proliferated the corporate boardroom agenda and companies’ leadership teams are trying to find ways to improve their social and environmental performance and enhance their corporate governance management systems. This paper investigates the main CSR and sustainability-related standards that modern corporations use. To do so, it uses a sample of the 60 companies listed in the ATHEX ESG index. Firstly, a content analysis of those companies’ sustainability reports is conducted. The 60 companies are categorized into sectors according to the Global Industry Classification Standard (GICS). The sustainability standards used by each sector are grouped into four categories, namely environmental, social, governance, and reporting. Furthermore, an attempt is made to establish a link between the standards used and both the sectors they belong to and the material topics of each sector as they emerge from each company’s materiality analysis. Our research shows that our sample companies predominantly utilize reporting standards regardless of their sector. We did not establish a definitive relation between the prioritized material topics and the relative standards employed by the companies. We may have recognized certain pairings such as environmental material topics with relative environmental management systems, but not in a rigid manner or across all material topic categories.